2020
DOI: 10.1590/1980-549720200016
|View full text |Cite
|
Sign up to set email alerts
|

Demografia, óbitos e indicadores de agravamento nas internações por intoxicações medicamentosas entre menores de 5 anos no Brasil

Abstract: RESUMO: Introdução: No Brasil, os medicamentos são os principais agentes causadores de intoxicação, e o maior número de casos desse problema envolve menores de 5 anos. Assim, o objetivo deste estudo foi descrever as internações por intoxicação medicamentosa nessa população quanto a sua demografia, óbitos e indicadores de agravamento. Métodos: Verificou-se a frequência das internações por intoxicação medicamentosa entre 2003 e 2012, utilizando os dados do Sistema de Informação Hospitalar. As variáveis utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…Approximately 17.2% of the patients presenting to emergency services have been reported to result in hospitalization, and 3-3.6% of these cases are admitted in pediatric intensive care unit. 8,9,24 In our study, no difference was found concerning hospitalization and intensive care requirement in both groups. Although mortality in pediatric poisonings varies across different centers, it is reported to be at 0.02-6%, with colchicine and tricyclic antidepressants being the deadliest agents.…”
Section: Discussioncontrasting
confidence: 48%
“…Approximately 17.2% of the patients presenting to emergency services have been reported to result in hospitalization, and 3-3.6% of these cases are admitted in pediatric intensive care unit. 8,9,24 In our study, no difference was found concerning hospitalization and intensive care requirement in both groups. Although mortality in pediatric poisonings varies across different centers, it is reported to be at 0.02-6%, with colchicine and tricyclic antidepressants being the deadliest agents.…”
Section: Discussioncontrasting
confidence: 48%
“…This is explained by the increased use of this product during the pandemic. This observation did not occur before the pandemic (Maior, Castro, Andrade, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…Three studies assessed the location of a child’s home as a risk factor for morbidity and/or mortality. A review of Brazilian national hospital data by Maior et al [ 54 ] described children aged 0-5 who presented after poisoning, and demonstrated a higher death to hospitalisation ratio among children from geographically remote regions (0.4% nationally compared to 1.1% and 0.6% in select remote regions, no significance testing done). Authors concluded that delayed access to care resulted in these differences in mortality due to an interplay of the geographic remoteness leading to prolonged travel times, fractured health infrastructure systems, and low socioeconomic resources [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…A review of Brazilian national hospital data by Maior et al [ 54 ] described children aged 0-5 who presented after poisoning, and demonstrated a higher death to hospitalisation ratio among children from geographically remote regions (0.4% nationally compared to 1.1% and 0.6% in select remote regions, no significance testing done). Authors concluded that delayed access to care resulted in these differences in mortality due to an interplay of the geographic remoteness leading to prolonged travel times, fractured health infrastructure systems, and low socioeconomic resources [ 54 ]. Dayasiri et al [ 50 ]in Sri Lanka reported that delayed presentation to care was associated with increased morbidity and mortality among children in their qualitative study, but did not provide statistics regarding this association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation